Prioriza SUS: Análise de problemas, recomendaç\~ao de estratégias e a vis\~ao do consórcio intergovernamental público como instrumento de reforço à Coordenaç\~ao Federativa do Sistema Único de Saúde - Sérgio F. Piola; Fabiola Sulpino Vieira; Luciana Mendes Santos Servo; Edvaldo Batista de Sá; Rodrigo Pucci de Sá ce Benevides (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– This text analyzes issues related to the federative coordination of the Unified Health System (SUS), with negative repercussions on access to public health goods and services, aiming at the identification and recommendation of measures that contribute to the gradual solution of access difficulties. Following the methodology of analysis of public policies, after the definition of the public problem as "difficulty of timely, effective and equitable access to public health goods and services" a tree of the problem was elaborated and several causes and consequences were identified. The cause chosen for intervention in this study is "insufficient federative coordination", which is also considered a structural problem of the SUS. One of the ways to reduce the problem of timely and equitable access to health care is to increase the availability of health goods and services in the most deprived areas. But this should be done in the most effective way, within the principles and guidelines of the SUS, based on a cooperative action among the federated entities. Thus, although there are other ways of expanding the public supply of health goods and services, it is understood that, in specific situations, the intergovernmental consortium is an option that cannot be ruled out. The preliminary proposal of this text was analyzed in a public policy forum with the participation of researchers, technicians and managers of the SUS, with recognized knowledge on the subject. The contributions of the forum participants were included in the text and summary of the discussions are inserted in appendix.
Keywords: I10; I18; 330; health policy; federative coordination in health; Unified Health System; public consortia